Structural and hydrogen isotope storage properties of Zr–Co–Fe alloy. (27th April 2015) - Jat, Ram Avtar; Singh, Ripandeep; Parida, S.C.; Das, A.; Agarwal, Renu; Mukerjee, S.K.; Ramakumar, K.L.
Abstract: In the present study, the effect of Fe substitution for Co on the hydrogen isotope storage properties of ZrCo alloy has been investigated to ascertain the improvement in durability of ZrCo alloy against hydrogen induced disproportionation. The ZrCo0.9 Fe0.1 alloy was synthesized by arc melting and characterized by X-ray diffraction analysis, SEM and EDS. Hydrogen isotope storage behavior of this alloy was probed by generating the hydrogen/deuterium desorption pressure–composition isotherms (PCIs) for ZrCo0.9 Fe0.1 –H2 /D2 systems. Thermodynamic parameters like enthalpy and entropy change for desorption of hydrogen/deuterium in the ZrCo0.9 Fe0.1 –H2 /D2 systems were derived from the van't Hoff plots. This study reveals the normal hydrogen isotope effect for this alloy, depicting the higher equilibrium pressure of D2 than that of H2 at all experimental temperatures. In addition, the cyclic life studies were also performed on ZrCo0.9 Fe0.1 alloy at 583 K up to 50 cycles of hydrogen/deuterium absorption–desorption. Neutron diffraction studies were also carried out on ZrCo0.9 Fe0.1 deuteride to determine its crystal structure and interstitial sites occupied by deuterium atoms. The experimental results show that Fe substitution increases the durability against hydrogen induced disproportionation as compared to pure ZrCo alloy, which makes it favorable for storage of hydrogen isotopes. Highlights: Hydrogen isotope effect on storage behavior of ZrCo0.9 Fe0.1 alloy was investigated. The alloy shows normal hydrogen isotope effect at all experimental temperatures. Thermodynamic parameters were calculated for the ZrCo0.9 Fe0.1 –H2 /D2 systems. ZrCo0.9 Fe0.1 alloy shows improved durability against hydrogen induced disproportionation. Crystal structure of ZrCo0.9 Fe0.1 deuteride was investigated by neutron diffraction method.